MON-021 Patterns of Sharps Handling and Disposal Among Insulin Using Patients with Diabetes - Montoya, Jordan (J Endocr Soc, 2019)
Background: Nearly 7 million patients with diabetes mellitus (DM) in the U.S. use insulin. Both Insulin therapy and self-monitoring of blood glucose (SMBG) have the potential to generate a large volume of biohazardous waste via use of “sharps” (needles and lancets). Unless safely disposed of these sharps could present a public health risk, placing unaware individuals at risk of needle sticks. However, there is a paucity of data on whether patients safely handle and dispose of used insulin needles and lancets. Objective: Assess patterns of sharps use and disposal among a clinic and hospital based population of DM patients on insulin therapy. Method: A survey was administered to a convenience sample of adult insulin treated DM patients recruited from an outpatient endocrinology clinic and an inpatient hospital setting. Patients were asked about patterns of sharps use (frequency of daily SMBG and insulin injections), how often sharps were used prior to disposal, sharp disposal technique, and education received regarding safe sharp disposal. Results: The survey was completed by 142 patients (94 outpatients and 48 inpatients). Mean age was 56 years, self-reported DM duration 20 years, hemoglobin A1c was 8.4%, and BMI 30.2 kg/m(2); 57% were men and 75% were white. No differences in characteristics (p>0.1) were seen between outpatient and inpatient respondents. The average number of insulin injections was 3/day, and frequency of SMBG was 3.5/day. A minority (22%) used an insulin needle 2 or more times, and 32% threw the needles directly into the garbage as opposed to a sealable or red sharps container. Most (56%) respondents used a lancet 2 or more times, sometimes changing the lancet once only every few months. Around a third (35%) threw used lancets directly into the garbage; one patient flushed them down the toilet. No differences were seen between outpatients and inpatients (p> 0.3) in patterns of needle use, lancet use, or disposal method. The majority (63%) of respondents indicated they had never received instruction on safe disposal of sharps. Conclusion: In this population of both outpatients and inpatients, repeated use of the same insulin needle and lancet was noted. Moreover, nearly a third of respondents disposed of their sharps in an unsafe manner. If similar data are confirmed in broader studies, this could translate into a large number of insulin using patients improperly disposing of their sharps waste—a potentially important public health hazard. With the rising prevalence of DM and need for insulin, further study is needed to determine sharps disposal practices of these patients. Improved education is needed on both a population and patient level regarding proper handling of these biohazardous materials.